2021
DOI: 10.1177/21501351211044129
|View full text |Cite
|
Sign up to set email alerts
|

The Failed Bidirectional Glenn Shunt: Risk Factors for Poor Outcomes and the Role of Early Reoperation

Abstract: Background: Bidirectional Glenn shunt (BDG) failure carries high morbidity and mortality but the clinical factors associated with failure and the optimal management strategy are understudied. Methods: A total of 217 patients undergoing BDG at our institution between 1989 and 2020 were retrospectively reviewed and categorized as success or failure. Failure was defined as the need for reoperation (BDG takedown, reoperation for correction of cardiac defect, and/or transplantation) at any time postoperatively; ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…However, some patients with inordinate hypoxemia may ultimately be treated with extracorporeal membrane oxygenation when collaterals are not successfully identified and closed. Greenberg and associates reported an increased risk for poor outcome when extracorporeal support is needed [6]. Further, Kendall and associates have reported that length of hospitalization after the SCPA is a risk factor for attrition before the total cavopulmonary anastomosis [7].…”
Section: Discussionmentioning
confidence: 99%
“…However, some patients with inordinate hypoxemia may ultimately be treated with extracorporeal membrane oxygenation when collaterals are not successfully identified and closed. Greenberg and associates reported an increased risk for poor outcome when extracorporeal support is needed [6]. Further, Kendall and associates have reported that length of hospitalization after the SCPA is a risk factor for attrition before the total cavopulmonary anastomosis [7].…”
Section: Discussionmentioning
confidence: 99%
“…Greenberg and colleagues demonstrated that 4 out of 6 (66.6%) patients died (n = 3) or needed heart transplantation (n = 1) after complete takedown. 22 We know that complete takedown is associated with substantial mortality, usually more than 50%. Additionally, we performed a total of 572 staged Fontan procedure between 1994 and 2021.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Furthermore, certain perioperative risk factors predispose patients to complications after the Glenn operation, and developing tools that allow for better prognostication could assist in both prognostication and surgical decision-making. 13 Thus, construction of an operation-specific TO for the Glenn operation may be particularly informative. Here, we aimed to define a TO for the Glenn operation and evaluated its ability to predict long-term outcomes and cost of care.…”
Section: Introductionmentioning
confidence: 99%